Stability Analysis and Optimal State Feedback Control of Back-to-Back Converter - Hassanzadeh, Fattah; Hajizadeh, Amin; Abbasi, Fazel (Journal of Technology Innovations in Renewable Energy, 2013)
Developing of transmission systems and using of different energy sources to supply the demand of network power makes that the using of power electronic converters are increased. Among the power electronic converters, Back to Back (B2B) converters are operated in the power system today’s widely. These converters can be located in connection of distributed power generation systems to power network and in HVDC transmission systems. In this paper stability analysis and controllability of B2B converters based on the average model in HVDC power transmission systems is studied. Also, optimal state feedback control under different conditions for B2B converter is proposed. Finally, simulation results are illustrated in order to verify the capability of proposed control strategy.